Cultura desviante e juventude: a torcida organizada como instrumento de domínio territorial - Flavia Cristina Soares (2018)
This thesis sought to demonstrate the settling process of a group of organized soccer fans in the capital of Minas Gerais state and, consequently, its divisions from a territorialized perspective. Through participant observation and in-depth interviews, it was possible to unravel that the group had as its objective of dominate the territory, preventing other groups of other organized fans from consolidating in the locality. To this end, young fans created the motto "together we are more" and their own symbols, forming a hierarchical structure, building the club's headquarters and developing activities such as meetings, charities, parties, and martial arts training. These made it possible to be recognized as a reference group within the organized crowd. In addition, it was possible to unveil a peculiar network of rivalries among young people belonging to the organized cheerleaders of Belo Horizonte, who share the same lifestyle oriented toward the construction of masculinities through the use of physical strength as an attribute of power. Lastly, it is highlighted that the traits conferred to the young organized fans as "criminals" or "rowdy" resulted from a well-succeeded transfer of stereotypes since the younger fans began to internalize what was expected from an organized supporter.